Sensory Analysis Of Breading Flour From Coconut Pulp With Different Drying Techniques - Syahputri, Nia Febi; Faridah, Anni; Syarif, Wirnelis; Mustika, Sari (Universitas Negeri Padang, 2023)
Coconut pulp is waste obtained from the by-products of coconut meat processing whose utilization is still limited. Coconut pulp contains 86.85% carbohydrates, 7.84% fat, 2.15% protein and 63.66% crude fiber. The nutritional content of coconut pulp has the potential to be processed into food products. The study aimed to analyze the use of different drying techniques with the addition of turmeric to the sensory and hedonic qualities of coconut pulp breading flour and its application to risoles. This study was a pure experiment with the Complete Randomized Design (CRD) method. Data were obtained from 5 limited panelists through organoleptic testing. Data were analyzed with ANAVA which showed the highest value trend and data that had significant differences continued with the Duncan test. The results of the best overall coconut pulp breading flour research were in the X3 treatment (dehydrator) covering aspects of aroma 3.27, taste 3.73 and hedonic 3.27, while the results of the best risoles research on average were found in treatment X3 (dehydrator) including color indicators 3.73, taste 3.80 and hedonics 3.33.